2010
DOI: 10.1211/jpp.62.06.0006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lipopeptides and iontophoresis on aciclovir skin delivery

Abstract: Surfactin and fengycin did not enhance aciclovir transport across the skin (not even when associated with iontophoresis) although they increased aciclovir concentration in the epidermis by a factor of 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Drugs with a wide range of molecular weights and water solubilities have demonstrated sustained release in a cubic phase, such as aspirin and vitamin E [82], propantheline bromide and oxybutynin hydrochloride [83], metronidazole [84], tetracycline [85], timolol maleate [86], chlorpheniramine maleate [87], propranolol hydrochloride [88], melatonin, pindolol, propranolol and pyrimethamine [89], hemoglobin [90], cefazolin [91], insulin [92, 93], capsaicin [26], cinnarizine [51, 94], and diclofenac salts [95]. Lee et al [73] studied the in vitro sustained release behavior of a number of model hydrophilic drugs with various molecular weights ( 14 C-glucose, Allura Red, and fluorescein isothiocyanate dextrans FD-4, FD-20, and FD-70) in two types of liquid crystalline matrixes, namely, V 2GMO (a cubic phase prepared from GMO) and V 2PT (a cubic phase prepared from PT).…”
Section: Applications Of Cubic and Hexagonal Liquid Crystals As Drmentioning
confidence: 99%
“…Drugs with a wide range of molecular weights and water solubilities have demonstrated sustained release in a cubic phase, such as aspirin and vitamin E [82], propantheline bromide and oxybutynin hydrochloride [83], metronidazole [84], tetracycline [85], timolol maleate [86], chlorpheniramine maleate [87], propranolol hydrochloride [88], melatonin, pindolol, propranolol and pyrimethamine [89], hemoglobin [90], cefazolin [91], insulin [92, 93], capsaicin [26], cinnarizine [51, 94], and diclofenac salts [95]. Lee et al [73] studied the in vitro sustained release behavior of a number of model hydrophilic drugs with various molecular weights ( 14 C-glucose, Allura Red, and fluorescein isothiocyanate dextrans FD-4, FD-20, and FD-70) in two types of liquid crystalline matrixes, namely, V 2GMO (a cubic phase prepared from GMO) and V 2PT (a cubic phase prepared from PT).…”
Section: Applications Of Cubic and Hexagonal Liquid Crystals As Drmentioning
confidence: 99%
“…These novel liposomes were described as safe and biologically decomposable, with suitable affinity for biological organisms, stable and with long service and shelf life. The potential of lipopeptides, fengycin and surfactin to act as enhancers for the transdermal penetration and skin accumulation of aciclovir was also recently investigated (Nicoli et al, 2010) to elucidate any possible synergistic effect between surfactin and fengycin associated with anodal iontophoresis. It was demonstrated that these lipopeptides did not enhance aciclovir transport across the skin (not even when associated with iontophoresis) although they increased aciclovir concentration in the epidermis by a factor of 2 (Nicoli et al, 2010).…”
Section: Biosurfactants Potential In Drug Deliverymentioning
confidence: 99%
“…The potential of lipopeptides, fengycin and surfactin to act as enhancers for the transdermal penetration and skin accumulation of aciclovir was also recently investigated (Nicoli et al, 2010) to elucidate any possible synergistic effect between surfactin and fengycin associated with anodal iontophoresis. It was demonstrated that these lipopeptides did not enhance aciclovir transport across the skin (not even when associated with iontophoresis) although they increased aciclovir concentration in the epidermis by a factor of 2 (Nicoli et al, 2010). Microemulsion produced using biosurfactant are thermodynamically stable and their isotropic systems that form spontaneously-consisting of microdomains of oil or water stabilized by an interfacial film -in addition to their long-term stability, easy preparation and high solubilization capacity are considered to be very promising liquid vehicles for future drug delivery systems (Date et al, 2008, as cited in Faivre & Rosilio, 2010.…”
Section: Biosurfactants Potential In Drug Deliverymentioning
confidence: 99%
“…The experiment was performed in triplicate or quadruplicate and the values were expressed as means ± SD. Statistical analysis of the effects of species differences and increasing current on the steady‐state skin permeation flux and the lag time was performed using a one‐way analysis of variance followed by Bonferroni's method [21,26] . Linear regression analysis was performed to examine correlation between the steady‐state skin permeation flux and current intensity.…”
Section: Methodsmentioning
confidence: 99%